Violence Against Women, Women Against Violence: Exploring the Experience of Women Who Have Participated in the Diamonds in the Ring Boxing Event in Aotearoa New Zealand - Roebuck, Ruby (Auckland University of Technology, 2023)
The sport of boxing is often viewed negatively and associated with violence, aggression, and masculinity (Davies & Deckert, 2018; Mayeda, 2008). Yet, women’s participation at a social and competitive level is increasing with research suggesting their experience may lead to a sense of personal development and empowerment (Hargreaves, 1997, Nash, 2019; Velija et al., 2013). Research has found that many women who have experienced domestic violence are not only choosing to participate in boxing and other combat sports but are also experiencing positive outcomes (Gammage et al., 2021; McCaughey, 1997; Velija et al., 2013), with some boxing-based programmes being implemented specifically for this social group (Van Ingen, 2011a, 2011b, 2016). However, no research to date has specifically explored this area within the New Zealand (NZ) context. In NZ, some survivors choose to participate in boxing, specifically Diamonds in the Ring (DITR). DITR is a boxing event that fundraises for the Women’s Refuge while “empowering families through fitness and boxing” (DITR, 2017). The women complete a 15-week boxing training camp that culminates in a fight exhibition. The purpose of this study is to gain an understanding of the experience of these women, to gauge their motivations and the extent to which their experience may have facilitated any form of personal development and empowerment. The study is guided by the following three research questions: 1) What motivates women who have been victims of domestic violence to participate in DITR? 2) In what way has their experience facilitated a sense of personal development? 3) If any, what aspects of their experience facilitated a sense of empowerment? A qualitative research design grounded in feminist criminological theory was utilised. One-on-one, in-depth, semi-structured interviews were conducted with five DITR participants who had survived domestic violence. The data were thematically analysed. The overarching theme is transformation, which consists of six sub-themes: 1) pre-transformation self-assessment, 2) physical development, 3) mental change, 4) identity shift: from victim to fighter, 5) empowerment, and 6) healing and recovery. In brief, the research questions were answered as follows. 1) Women were motivated to participate in DITR for several reasons, including, to support a friend, for personal growth and development, and to support the Women’s Refuge. 2) Participants experienced a strong sense of personal development characterised by physical and mental strength, self-confidence, self-esteem, change in mindset, and overall positive wellbeing. 3) There was a clear indication that participants experienced a strong sense of empowerment which was facilitated by the development of strength, voice and agency, a shift in mindset, and a sense of healing and recovery from past trauma. Collectively, these developments represented a transformation that culminated into an identity shift in which the strong, empowered woman they felt they had become was very different to who they were when they entered DITR. The study concludes that boxing is a powerful facilitator of change, however, one of the key contributions to this change was the contact aspect of boxing training. As this raises questions around the vulnerability of survivors of violence and the need to potentially reframe our thinking about this demographic, further research is required to determine whether this finding extends more broadly to other women survivors of violence and other combat sports.